Genotyping-by-Sequencing Facilitates a High-Density Consensus Linkage Map for Aegilops umbellulata, a Wild Relative of Cultivated Wheat. Issue 5 (1st May 2017) - Edae, Erena A; Olivera, Pablo D; Jin, Yue; Rouse, Matthew N
Abstract: High-density genetic maps are useful to precisely localize QTL or genes that might be used to improve traits of nutritional and/or economical importance in crops. However, high-density genetic maps are lacking for most wild relatives of crop species, including wheat. Aegilops umbellulata is a wild relative of wheat known for its potential as a source of biotic and abiotic stress resistance genes. In this work, we have developed a framework consensus genetic map using two biparental populations derived from accessions PI 298905, PI 542369, PI 5422375, and PI 554395. The framework map comprised 3009 genotype-by-sequence SNPs with a total map size of 948.72 cM. On average, there were three SNPs per centimorgan for each chromosome. Chromosome 1U was the shortest (66.5 cM), with only 81 SNPs, whereas the remaining chromosomes had between 391 and 591 SNP markers. A total of 2395 unmapped SNPs were added to the linkage maps through a recombination frequency approach, and increased the number of SNPs placed on the consensus map to a total of 5404 markers. Segregation distortion was disproportionally high for chromosome 1U for both populations used to construct component linkage maps, and thus segregation distortion could be one of the probable reasons for the exceptionally reduced linkage size for chromosome 1U. From comparative analysis, Ae . umbellulata chromosomes except 4U showed moderate to strong collinearity with corresponding homeologous chromosomes of hexaploid wheat and barley. The present consensus map may serve as a reference map in QTL mapping and validation projects, and also in genome assembly to develop a reference genome sequence for Ae. umbellulata .